TENSI SEKTARIANISME DAN TANTANGAN DEMOKRASI DI TIMUR TENGAH PASCA ARAB SPRING - Sainul Rahman (IAIN Ambon, 2019)
ABSTRACT The Arab Spring wave in the beginning of 2011 that hit Middle Eastern countries, started from Tunisia, Egypt, Libya, Yemen, and Syria, which still continue to this day, is a symbol of the fall of authoritarian and repressive Arab regimes, as well as a symbol of the struggle of Arabian people who want great changes in various fields such as economic, social, and democratic political system. After eight years, the Arab Spring still has many problems, Middle Eastern countries still trapped in conflict and civil war. The transition of democracy that hoped is not going well, trapped in sectarian interests: tribes, religions, streams (madzhab), and political groups. Sectarianism has become one of the causes of instability and colored the politic dynamics in the region. In fact, it socially and historically has multiple roots over a long period of time in the Middle East. This paper seeks to read the history and dynamics of sectarian conflict, as well as the process of democratic transition: between opportunities and challenges, and the realization of democracy in the region after the Arab Spring. Keywords: Sectarianism, Democracy, Arab Spring, Middle East. ABSTRAK Gelombang Arab Spring pada awal 2011 yang melanda negara-negara Timur Tengah, dimulai dari Tunisia, Mesir, Libya, Yaman, dan Suriah yang masih berlanjut hingga kini, adalah sebuah simbol jatuhnya rezim-rezim Arab yang otoriter dan represif, dan juga sebagai simbol perjuangan rakyat Arab yang menginginkan adanya perubahan besar dalam berbagai bidang, ekonomi, sosial, sistem politik terbuka dan demokratis. Setelah delapan tahun semenjak bergulirnya, Arab Spring masih menyisakan banyak problem, negara-negara Timur Tengah masih terpuruk, terjebak dalam konflik dan perang saudara. Transisi demokrasi yang dicita-citakan tidak berjalan dengan baik, tersandera oleh kepentingan-kepentingan sektarian: suku, agama, mazhab dan kelompok politik. Sektarianisme menjadi salah satu penyabab instabilitas dan telah mewarnai dinamika politik di kawasan Timur Tengah. secara sosio-historis sektarianisme di Timur Tengah memiliki akar yang berlapis-lapis dalam kurun waktu yang panjang. Tulisan ini berusaha untuk membaca sejarah dan dinamika konflik sektarisnisme, proses transisi demokrasi: antara peluang dan tantangan, dan realisasi demokrasi di Timur Tengah pasca Arab Spring. Kata Kunci: Sektarianisme, Demokrasi, Arab Spring, Timur Tengah.